Usability, Acceptability, and Satisfaction of Indonesian Birth Attendant Practitioners Using the 2020 World Health Organization Labor Care Guide - adjie, Josef Maria Seno; Indrianie, Sisca (Indonesian Journal of Obstetrics and Gynecology, 2025)
Objectives: This study was conducted to determine whether the World Health Organization Labor Care Guide 2020 (WHO LCG 2020) can be accepted and implemented by Indonesian birth attendant practitioners.Methods: This study is mixed-method research, with a quantitative study using a cross-sectional design and a qualitative study using an in-depth interview design. The study was conducted from July to November 2023 in Dr. Cipto Mangunkusumo General Hospital and associated teaching hospital. The subjects in this study were birth attendant practitioners who had received training in the use of partographs or normal delivery care (APN). Data analysis was performed descriptively to determine the distribution and characteristics of practitioners and patients, which will be presented in a tabular form. Data from the interviews were reported narratively.Results: Fifty-nine participants (45 midwives and 14 doctors) received training in the use and filling of the LCG sheet. The participants used the LCG for 120 patients, with the majority of patients having spontaneous vaginal births (78.3%). From the results of the questionnaire, 40 participants (67.8%) felt that the LCG sheet was useful and 42 participants (71.2%) felt satisfied. Overall, most participants felt that the LCG sheet was useful and satisfied with its use in helping health workers assist in childbirth.Conclusion: It was found that regular training is needed on how to complete the WHO LCG 2020 sheet, and a lot of experience is required to become accustomed to using the LCG new birth monitoring format. Keywords: birth attendant, childbirth, doctors, labor care guide, midwives